2021
DOI: 10.3390/nu13061992
|View full text |Cite
|
Sign up to set email alerts
|

Relative Efficacy of Weight Management, Exercise, and Combined Treatment for Muscle Mass and Physical Sarcopenia Indices in Adults with Overweight or Obesity and Osteoarthritis: A Network Meta-Analysis of Randomized Controlled Trials

Abstract: Aging and osteoarthritis are associated with high risk of muscle mass loss, which leads to physical disability; this loss can be effectively alleviated by diet (DI) and exercise (ET) interventions. This study investigated the relative effects of different types of diet, exercise, and combined treatment (DI+ET) on muscle mass and functional outcomes in individuals with obesity and lower-limb osteoarthritis. A comprehensive search of online databases was performed to identify randomized controlled trials (RCTs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 103 publications
1
3
0
Order By: Relevance
“…Both the Asian Working Group for Sarcopenia Standards (AWGS) and the 2nd Edition of the European Working Group on Sarcopenia Standards (EWGSOP2) include walking speed as the diagnosis criteria of sarcopenia. The results of this study confirm that exercise can effectively increase the walking speed of the target group, which is consistent with previous studies [61][62][63]. However, a relatively higher level of heterogeneity existed among the included studies.…”
Section: Discussionsupporting
confidence: 91%
“…Both the Asian Working Group for Sarcopenia Standards (AWGS) and the 2nd Edition of the European Working Group on Sarcopenia Standards (EWGSOP2) include walking speed as the diagnosis criteria of sarcopenia. The results of this study confirm that exercise can effectively increase the walking speed of the target group, which is consistent with previous studies [61][62][63]. However, a relatively higher level of heterogeneity existed among the included studies.…”
Section: Discussionsupporting
confidence: 91%
“…RCTs found that for overweight patients with OA, both resistance exercise and aerobic exercise can effectively increase the patient's muscle mass, muscle strength, and walking speed, and the effect is even better if the combination of diet therapy and exercise [43]. Protein-rich nutritional composition supplementation combined with resistance exercise training can improve joint function and muscle loss index in older women with knee osteoarthritis [44].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of sarcopenia and osteoarthritis is escalating [33]. The therapeutic role of exercise rehabilitation in these diseases is garnering an increasing body of evidence, thereby driving a rapid surge in demand, particularly for addressing the co-occurrence of sarcopenia and osteoarthritis [34,35]. The objective of this trial is to assess the clinical outcome of an AI-generated, wearable devicebased rehabilitation program relative to traditional clinic-based rehabilitation in a PROBE non-inferiority design.…”
Section: Discussionmentioning
confidence: 99%